Impacts of irrigation management transfer: a review of the evidence - Vermillion, Douglas L. (International Irrigation Management Institute, 1997)
Evaluates data from 29 different studies on irrigation management transfer to assess the impacts of transfer on various aspects of irrigation system management. Twelve guiding principles to ensure a more systematic approach to research on the impacts of management transfer are proposed. Identifies key research propositions on the conditions necessary for transfer programs to succeed.